OC-074 Enhanced recovery for oesophagogastric surgery (eros). (22nd June 2015) - Underwood, T; Noble, F; Hole, R; Sharland, D; Kelly, J; Byrne, J
Abstract : Introduction: Enhanced recovery is an accepted mechanism to improve perioperative outcomes in surgery. The generalisablity of outcomes after enhanced recovery for oesophagogastric surgery (EROS) has been limited because the majority of series come from a single surgeon or have excluded patients based on surgeon preference. There have been few reports comparing open with minimally invasive surgery in this setting. We review our experience of EROS for all-comers and compare minimally invasive two-stage oesophagectomy (MIO-2) with open Ivor Lewis oesophagectomy (IVL). Method: The EROS perioperative programme at University Hospital Southampton commenced with a multidisciplinary team meeting followed by multiple rounds of protocol revision, including patient feedback, to include all aspects of the perioperative pathway. All patients undergoing oesophageal or gastric resections were entered into EROS from 20/9/13. Short-term clinicopathologic outcomes were recorded using validated systems. Results: 78 patients in EROS have undergone the following operations: subtotal gastrectomy (5 patients), total gastrectomy (14), Mckeown oesophagectomy (1), colonic interposition (1), MIO-2 (29), IVL (23), hybrid MIO-2 (5). Overall median length of hospital stay was 9 days (range 4–47) with no deaths. Considering oesophagectomy, patient demographics (age, sex, preoperative body mass index, tumour characteristics, neoadjuvant regime and pathological tumour stage) were comparable between MIO-2 and IVL. ASA grade was higher in patients who underwent MIO-2 (P < 0.05). Adherence to the EROS protocol was equivalent between groups (MIO-2 vs. IVL): EROS commenced in pre-assessment (95.7% vs. 93.1%), Hillrom chair-bed use (90.9% vs. 92.9%), EROS carried out in HDU (90.9% vs. 85.7%). Outcomes for MIO-2 and IVL were comparable for median length of stay (8 [range 6–47] vs. 9 [7–16] days), anastomotic leak (1/28 vs. 0/23), and complications graded by the Clavien-Dindo classification (Grade 1: 13% vs. 3.6%; Grade 2: 56.5% vs. 50%; Grade 3: 3.6% vs. 0%; Grade 4: 7.1% vs. 0% with no complications in 30.4% vs. 35.7% of patients respectively). One patient remains on EROS day 6 post MIO-2. Oncological parameters were comparable between MIO-2 and IVL: resection margin clearance (R0) (71.4% vs 86.4%) and median lymph node yield (28 (range 12–62) vs. 25 (8–64)) respectively. Conclusion: The introduction of EROS for all patients undergoing oesophageal surgery has led to significant patient benefits, including reduced hospital stay (12 days to 9 days) and fewer postoperative major complications (19.8% to 5.9%) compared to our previously published series. Within EROS open oesophageal resection has comparable outcomes to minimally invasive surgery. Disclosure of interest: T. Underwood Grant/ Research Support from: MRC, F. Noble Grant/ Research Support from: Cancer Research UK, R. Hole: None Declared, D. Sharland: None Declared, J. Kelly: None Declared, J. Byrne: None Declared.